Birch bark pieces stored on a wooden spike at Straumen Farm, Norway - Campbell, Sandy (2024)
Birch bark had many uses, but one of the most important was as roofing material on sod roofed buildings in Arctic regions. A waterproof layer of birch bark was nailed to the roof and the sod placed on top to protect it. These pieces are too small for roofing.